Answers

2016-04-19T11:55:15+05:30
To factor :ax² + bx + c , 
1) Find the product of 1st and last term( a x c). 
2)Find the factors in a way that 
addition or subtraction of that factors is 
3) Write the middle term using the sum of the 
two new factors, including proper signs.
4) Group the terms to form pairs Factor each pair by finding common factors.
5) Factor out the shared terms.


0
2016-04-19T23:12:39+05:30
Example 1: x² + 5x + 6

x² + 5x + 6
=x² + 2x + 3x + 6
=x(x+2) + 3(x+2)
=(x+2)(x+3)

Example 2: x² - 5x + 6

x² - 5x - 6
=x² - 2x - 3x + 6
=x(x-2) -3(x-2)
=(x-2)(x-3)

Example 3: x² + x - 6

x² + x - 6
=x² + 3x - 2x - 6
=x(x+3) -2(x+3)
=(x+3)(x-2)

Example 4: x² - x - 6

x² - x - 6
=x² -3x + 2x - 6
=x(x-3) +2(x-3)
=(x-3)(x+2)



0